PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO, EARNING PER SHARE, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013 - 2015) - Sundari Tri Utami Wijayanti, 13.05.52.0162; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2017)
This study aims to examine the effect of Return On Assets, Debt To Equity Ratio, Earnig Per Share, Company Size and Liquidity to the value of companies in Manufacturing companies in Indonesia Stock Exchange. The population of this study is a Manufacturing company listed on the Indonesia Stock Exchange (IDX) during the year 2013-2015 which reports the value of the company. The sample included in this research criteria is 270 companies by using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis with SPSS 20 program.The results showed that the variable return on asset and earnings per share have a significant positive effect on firm value, firm size has a significant negative effect on firm value, debt to equity ratio has positive effect not significant to firm value, while liquidity has negative effect not significant to firm value.Keywords: Firm Value, Retun On Asset, Debt To Equity Ratio, Earning Per Share, Company Size and Liquidity